2021
DOI: 10.3390/jof7110985
|View full text |Cite
|
Sign up to set email alerts
|

Global Prevalence of COVID-19-Associated Mucormycosis (CAM): Living Systematic Review and Meta-Analysis

Abstract: Mucormycosis, a secondary fungal infection, gained much attention in the ongoing COVID-19 pandemic. This deadly infection has a high all-cause mortality rate and imposes a significant economic, epidemiological, and humanistic burden on the patients and healthcare system. Evidence from the published epidemiological studies showed the varying prevalence of COVID-19-associated mucormycosis (CAM). This study aims to compute the pooled prevalence of CAM and other associated clinical outcomes. MEDLINE, Embase, Cochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 79 publications
1
53
1
6
Order By: Relevance
“… 36 Although glucocorticoids are a risk factor for both CAPA and CAPM, 83 poorly controlled diabetes is more often associated with CAPM than with CAPA. 4 , 5 , 26 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 36 Although glucocorticoids are a risk factor for both CAPA and CAPM, 83 poorly controlled diabetes is more often associated with CAPM than with CAPA. 4 , 5 , 26 …”
Section: Resultsmentioning
confidence: 99%
“… 2 During the COVID-19-associated mucormycosis (CAM) outbreak, rhino-orbital mucormycosis was the most common manifestation, followed by pulmonary mucormycosis. 3 , 4 , 5 Among the various risk factors for rhino-orbital mucormycosis and pulmonary mucormycosis, uncontrolled diabetes overshadowed all others. 3 In two large multicentre cohort studies from India, pulmonary mucormycosis accounted for 13·3% of the total patients with mucormycosis before the COVID-19 pandemic, and 8·6% of the total patients with mucormycosis during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…A pre-pandemic study showed an increased incidence (about 2.5 times) of mucormycosis during the years 2008–2014 in Iran [ 81 ]. Besides, this infection has become 50 times more prevalent in the COVID-19 era globally [ 82 ]. CAM has been primarily seen in India, while cases from other countries, including Iran, have also been reported [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, this infection has received scarce attention because of the low number of cases in comparison with other more frequent fungal infections, but the emerge of the SARS-CoV-2 disease (COVID-19) pandemic has increased the incidence of fungal infections, rising the concern about their risks ( Ghosh et al., 2021 ). The upsurge in COVID-19-associated mucormycosis with a prevalence 50 times higher than the uppermost recorded data ( Hussain et al., 2021 ) has highlighted the unmet need to better understand mucormycosis ( Stone et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%